PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PERBANKAN - Mentiana Sibarani; Ivena Melinda (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the relationship between the disclosure of corporate social responsibility and financial performance in the banking sector in Indonesia. Samples from this study that reveals the company sustainability report and companies listed on the Indonesian Stock Exchange (BEI). Consisting of 11 companies during the period 2015-2017 and the research had a total of 33 samples. This study uses secondary data from annual reports and sustainability reports banking firm period 2015-2017. In this study testing the effect of disclosure of corporate social responsibility on the financial performance is done using simple linear regression testing. The results showed the disclosure of corporate social responsibility mempegaruhi not significantly affect the financial performance. The results showed the disclosure of corporate social responsibility do not significantly affect the financial performance. This suggests that in addition to the disclosure of corporate social responsibility there are several things that affect financial performance. In this study testing the effect of disclosure of corporate social responsibility on the financial performance is done using simple linear regression testing. The results showed the disclosure of corporate social responsibility do not significantly affect the financial performance.